New Institutionalism: Identifying Informal Institutions in the Political Process of Pakistan - Muhammad Ayub Jan; Syed Sami Raza (Journal of Political Studies, 2015)
This paper focuses on a recent theoretical perspective and approach in the study of political institutions–‘new institutionalism’. The primary aim of the paper is to illustrate the theoretical assumptions of ‘new institutionalism’ with empirical evidence from Pakistan. The paper illustrates the theoretical assumptions of new institutionalism especially its distinction between formal and informal institutions. New institutionalism is quite distinctive in its emphasis on informal institutions rather than on formal ones. This study delineates such distinction by placing it in the context of political processes and structures in Pakistan. The paper argues that political processes and structures in Pakistan exhibit considerable presence of informal institutions though they often go unnoticed and along with them their influence on democratic governance. We expect that this paper will contribute to the existing literature by focusing on informal institutions, which does not get much attention in academic writings on the political process in Pakistan.